The Role of the Gorontalo District National Land Agency Service in the Implementation of the Systematic Complete Land Registration Program (PTSL) (Faculty of Law, Universitas Negeri Semarang, 2020)
The purpose of Complete Systematic Land Registration (PTSL) is to accelerate the provision of legal certainty and legal protection of community land rights in a certain, simple, fast, smooth, safe, fair, equitable and open manner and accountable, so as to improve the welfare and prosperity of the community and the country’s economy in Gorontalo district. The formulation of the issues raised by this problem are (1). How is the role of the National Land Agency Kab. Gorontalo in the Implementation of the Systematic Complete Land Registration Program (PTSL) (2). What are the obstacles faced by the Gorontalo District Land Office in implementing the Systematic Complete Land Registration program (PTSL) in Gorontalo District and the Solution to overcome these obstacles. This study uses a research approach that is empirical juridical to analyze various laws and regulations related to the role of Gorontalo District Land Office in an effort to improve land rights. And to analyze the law which is seen as a behavior of people who are patterned in the lives of people who always interact and relate in social aspects. The results of this study conclude that in the implementation of this complete systematic land registration carried out by the Gorontalo District National Land Agency, it has been implemented well in accordance with the targets that have been targeted by the central government, although there are some obstacles found in the field in the framework of accelerating the implementation of the Systematic Land Registration Program Complete (PTSL).